The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0165396
|View full text |Cite
|
Sign up to set email alerts
|

Double Trouble: Prevalence and Factors Associated with Tuberculosis and Diabetes Comorbidity in Bangladesh

Abstract: BackgroundDiabetes among tuberculosis patients increases the risk of tuberculosis treatment failure, death, and development of multidrug-resistant tuberculosis. Yet, there is no data is available in Bangladesh on the prevalence of diabetes among tuberculosis patients. The objective of the current study was to estimate prevalence and identify factors associated with tuberculosis-diabetes co-morbidity among TB patients enrolled in the Directly Observed Treatment, Short course program.MethodsA community based cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
4
25
2
5
Order By: Relevance
“…Notably, older age, sex, educational attainment, occupational status, wealth status, BMI and geographic location were significantly associated with NCDs in the present study which is consistent with the findings of other developing countries 43–50. Like earlier studies, we also found that the risk factors of having comorbidity were significantly associated with older age, sex, higher educational level, regional variation, higher BMI (eg, overweight, obese) and the working status of individuals 32 51 52. This may be a result of older people often suffering from various health issues such as reduced physical activities, poor nutritional status and poor immunity 53.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, older age, sex, educational attainment, occupational status, wealth status, BMI and geographic location were significantly associated with NCDs in the present study which is consistent with the findings of other developing countries 43–50. Like earlier studies, we also found that the risk factors of having comorbidity were significantly associated with older age, sex, higher educational level, regional variation, higher BMI (eg, overweight, obese) and the working status of individuals 32 51 52. This may be a result of older people often suffering from various health issues such as reduced physical activities, poor nutritional status and poor immunity 53.…”
Section: Discussionsupporting
confidence: 91%
“…[ 5 6 7 20 21 22 23 24 ] Similar to other studies, the prevalence of diabetes in TB patients in our study was significantly higher in the older age group (>50 years), males, smokers, and overweight (BMI >25) patients. [ 5 6 7 20 21 22 23 24 25 26 27 28 29 ] In the current study, similar to a study in the United States, the socioeconomic status was not significantly associated with the presence of diabetes in TB patients. [ 30 ] We also found that diabetes was significantly more common in patients with pulmonary TB and type II treatment category patients.…”
Section: Discussionsupporting
confidence: 72%
“…Findings from subgroup analysis showed that there is a wide difference between the pooled prevalence across the countries; the lowest being 11% (95% CI 10.0, 12.0) in Bangladesh to the highest 24% (95% CI 21.0, 27.0) in Sri-Lanka. Similarly, a large variation in the diabetes prevalence was also seen within countries, ranging from 5% (95% CI 3.0, 8.0) 13 to 66% (95% CI 61.0, 71.0) 32 in India, 8%, (95% CI 4.0, 14.0) 76 to 40% (95% CI 38.0, 41.0) 68 in Pakistan, 4% (95% CI 2.0, 6.0) 80 to 25% (95% CI 21.0, 29.0) 78 in Nepal and 8% (95% CI 7.0, 10.0) 82 to 13% (95% CI 11.0, 14.0) 83 in Bangladesh (Table 1 ). Furthermore, a small reduction in the pooled prevalence of diabetes among the TB population was observed in the pooled analysis of studies limited to more than 300 participants only (19.0%, 95% CI 16.0, 22.0) and studies conducted within 2010–2015 (19.0%, 95% CI 16.0, 22.0).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were judged at a high risk of bias for item number three of the selection category description of the non-response rate. Only 12 studies have adequately described the non-response rate in the study 21 , 24 , 27 , 32 , 37 , 38 , 40 , 51 , 56 , 64 , 79 , 83 (Supplementary Table 3 ). The mean NOS score assessing the impact of diabetes among TB treatment outcome was seven (of a possible nine points), suggesting that the high quality of the studies was included in the meta-analysis (Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation